The Value of Islamic Religiosity in the Migration of Admiral Cheng Ho in Archipelago, Indonesia - Auza, Ara; Andary, Ria Wuri; Tamsil, Ilma Saakinah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to explain the value of Islamic religiosity in Admiral Cheng Ho's migration to Nusantara, Indonesia. This research uses library research. The descriptive analysis method collects, compiles, analyzes, and draws conclusions. The results showed that China communicated Islamic culture as an effective way to be accepted in the archipelago. The migration step of Chinese diplomacy through Admiral Cheng Ho is said to have reflected the